2015
DOI: 10.15420/cfr.2015.1.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Patient Self-Management In Chronic Heart Failure — Establishing Concordance Between Guidelines And Practice

Abstract: The gold-standard of patient self-management in chronic heart failure (CHF) can be defined as "daily activities that maintain clinical stability". 1 This requires that patients monitor their symptoms, adhere to their medication, diet and exercise regimens and manage symptoms by recognising changes and responding by either adapting behaviours or by seeking appropriate assistance.2 Patient self-management is linked to reduced mortality risk and fewer hospital admissions; however, there is less certainty with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 53 publications
0
52
0
8
Order By: Relevance
“…Based on the guidelines reported by the European Society of Cardiology for the diagnosis and treatment of acute and chronic heart failure [ 9 ], adherence to self-care is an important component of improving patient outcomes—reducing mortality and improving the quality of life. Therefore, guidelines on heart failure management place a strong emphasis on adherence to self-care behaviors such as lifestyle modifications and fluid restrictions [ 10 ]. Recent reviews on the impact of heart failure self-management interventions highlight their beneficial effects in reducing rates of heart failure specific readmission and mortality, as well as improving heart failure-related quality of life [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the guidelines reported by the European Society of Cardiology for the diagnosis and treatment of acute and chronic heart failure [ 9 ], adherence to self-care is an important component of improving patient outcomes—reducing mortality and improving the quality of life. Therefore, guidelines on heart failure management place a strong emphasis on adherence to self-care behaviors such as lifestyle modifications and fluid restrictions [ 10 ]. Recent reviews on the impact of heart failure self-management interventions highlight their beneficial effects in reducing rates of heart failure specific readmission and mortality, as well as improving heart failure-related quality of life [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise training enhances myocardial function and exercise tolerance, improves ventilation and has favourable effects on haemodynamics in HF. 17 Existing paper-based self-monitoring methods are inefficient, difficult to share and poorly adhered to. 15 The HF-ACTION randomised control trial found that exercise was associated with a 13% risk reduction in HF mortality and hospitalisations.…”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, exercise training has a favourable effect on symptoms (MLWHF Questionnaire general well-being score 2.6 AE 1.4 vs 4.0 AE 0.5, P < 0.01). 17 Electronic platforms have an increasingly relevant role in the provision of healthcare. 16 Recent studies suggest feasibility of mobile technology in self-monitoring physical activity trends and have demonstrated enhanced participation and motivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations